Congenital hypotrichosis caused by compound heterozygous variants in the LSS gene in a Chinese patient with strabismus: case report - Bao, Linlin; Li, Qian; Yue, Zhicao; Yang, Fang (Frontiers in Pediatrics, 2025)
BackgroundLanosterol synthase (LSS) is essential for cholesterol biosynthesis and impacts embryonic development and growth. LSS gene variants have been associated with various conditions such as congenital hypotrichosis and cataracts, but the genotype-phenotype relationship remains not well understood.Case presentationHerein, we report an 8-year-old boy presenting with congenital hypotrichosis and intermittent exotropia, but without any ocular movement abnormalities or cataracts. His hair exhibited sparse distribution with a yellow color, reduced strength, and minimal growth. Scanning electron microscopy revealed abnormal keratinization of the hair shafts, characterized by irregular, jagged scales and raised edges. Whole-exome sequencing identified compound heterozygous missense variants in the LSS gene: c.1303C>T (p.Arg435Cys) and c.386G>A (p.Arg129Gln). Three-dimensional protein modeling revealed that these variants affect highly conserved amino acid residues and are predicted by computational tools to destabilize the protein. Based on ACMG guidelines, both variants were classified as likely pathogenic, consistent with the patient's phenotype.ConclusionWe present a rare case of LSS-related hypotrichosis with strabismus and a novel c.386G>A variant has not been reported, which broadens the understanding of LSS gene variants and their phenotypic spectrum, enhancing insights into the genotype-phenotype relationship in LSS-related conditions.